Influence of International Price, Domestic Price and Total Production of Indonesian Crude Palm Oil on the Export Volume Of Indonesian Crude Palm Oil in 2019-2023 - Arvia Nur Arofah; Karnowahadi; Sri Eka Sadriatwati (Politeknik Negeri Semarang, 2025)
The plantation subsector contributes significantly to Indonesia's Gross Domestic Product (GDP). Crude palm oil, as a leading commodity, contributes greatly to GDP and is a major source of foreign exchange earnings. This research examines the impact of international prices, domestic prices, and total production of Indonesian crude palm oil on the export volume of Indonesian crude palm oil from 2019 to 2023. The type of data used in this research is secondary quantitative time series data obtained from the Central Bureau of Statistics, the World Bank, and the Directorate General of Plantations. The analysis methods used include descriptive statistics, classical assumption tests, and multiple linear regression analysis with SPSS 25.0 analysis tools. The results showed that international prices do not effect on export volume, while domestic prices have a negative and significant effect, and total production has a positive and significant effect on the export volume of Indonesian crude palm oil. Subsektor perkebunan berperan besar terhadap Produk Domestik Bruto (PDB) Indonesia. Minyak kelapa sawit mentah sebagai komoditas unggulan memberikan peranan yang besar terhadap PDB dan menjadi sumber utama pendapatan devisa negara. Penelitian ini menganalisis pengaruh harga internasional, harga domestik dan jumlah produksi terhadap volume ekspor minyak kelapa sawit Indonesia tahun 2019-2023. Jenis data yang digunakan dalam penelitian ini adalah data kuantitatif sekunder time series yang diperoleh dari BPS, World Bank, dan Direktorat Jenderal Perkebunan. Metode analisis yang digunakan meliputi statistik deskriptif, uji asumsi klasik dan analisis regresi linier berganda dengan alat bantu analisis SPSS 25.0. Hasil penelitian menunjukkan bahwa harga internasional tidak berpengaruh terhadap volume ekspor, sementara harga domestik berpengaruh negatif dan signifikan dan jumlah produksi berpengaruh positif dan signifikan terhadap volume ekspor minyak kelapa sawit Indonesia.